Magnetic Properties of Composites Based on the Intercalation of Znii and Cuii Bimetallic Macrocyclic Complexes in the mnps3 Phase - Venegas-Yazigi, D; Venegas-Yazigi, D (Royal Society of Chemistry, 2017)
Asymmetric macrocyclic complexes of the type [M2LCl2]·xH2O have been obtained and intercalated using the potassium precursor phase K0.4Mn0.8PS3·H2O (M: ZnII or CuII; LH2: macrocyclic ligand derived from 2-hydroxy-5-methyl-1,3-benzenedicarbaldehyde and two different amines, namely, ethylenediamine and o-phenylenediamine). The intercalation of the layered phase K0.4Mn0.8PS3·H2O by the macrocyclic species was carried out by a microwave-assisted reaction and enabled the partial exchange of the hydrated potassium ions located in the interlayer space to obtain the composites K0.32[Zn2L]0.04Mn0.8PS3 (1) and K0.24[Cu2L]0.08Mn0.8PS3 (2). These magnetic materials were studied by DC and AC magnetization measurements and electron paramagnetic resonance (EPR) spectroscopy. In comparison with the potassium precursor, both composites gave rise to broader and less intense spontaneous magnetization curves at low temperatures. The composite K0.32[Zn2L]0.04Mn0.8PS3 (1) exhibited spontaneous magnetization in the form of one broad asymmetric maximum at 27 K. However, K0.24[Cu2L]0.08Mn0.8PS3 (2) had two defined maxima at 24 and 12 K. The observation of a maximum in the imaginary part of the AC susceptibility data implies the existence of a spin canting phenomenon that would be responsible for the spontaneous magnetization. The EPR results are qualitatively consistent with the magnetization data and reveal that exchange narrowing effects were responsible for the narrowing and broadening of the line shapes. © 2017 The Royal Society of Chemistry.